Development and Problems of Insurer Accounting when Passing from Varied Practices to Generally Accepted Principles - Mihailova, Mariana (Research Papers, 2006)
The objects of the research in this study are the stages of development of insurer accounting, connected problems and possibilities of achieving of comparable and reliable accounting information. The existing traditions and imposed practices in insurer accounting have been studied, including the influence of Directives of European Union. The applied approaches, harmonization and standardization in accounting practices and their impact on development of insurer accounting and its legal framework have been analyzed. The effective International Financial Reporting Standard 4Insurance Contracts (effective date 01.01.2005) is presented as realization of the first stage of harmonization of insurer accounting and as an expression of contemporary processes of convergention and globalization in the sphere of accounting.